A New Species of Diploderma (Reptilia: Squamata: Agamidae) from the upper Salween River in Eastern Tibet, China - Wang, Kai; Zhang, Yinpeng; Li, Xianqi (Zootaxa, 2022)
A new species of Diploderma is described from the upper Salween River Valley in eastern Tibet, China based on morphological and genetic data. The new species is morphologically most similar and phylogenetically closely related to D. laeviventre, but it can be easily diagnosed by having distinct conical scales on the post rictal region of the head, distinctively keeled ventral head and body scales, and different coloration of gular spots and dorsolateral stripes in both sexes. The taxonomic discovery further highlights the underestimated diversity of the genus and the importance of habitat conservation of the neglected hot-dry valley ecosystems in the Hengduan Mountain Region of China.